Rope climbing robot - Muhammad Za'im Atif Bin Che Ahmad Zaini (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
The objective of this project is to design a robot that can climb a rope either vertically or horizontally by itself. This robot is built with combination of hardware and software interfaces. Arduino is used as the brain of the robot. In addition, the servos motor, DC motor and limit switches as sensor for detect the obstacle are used in this robot. Basically, the robot programming is designed so that the robot is able to climb a rope either in upward or backward direction and it also to detect if there is any obstacles while in climbing motion. The rope climbing robot is very effective for climbing proposes especially to places which is dangerous for human or place where human could not be reached.